Strategies for Handling Bullying in Elementary School Children in the School Environment - Kristina Handayani; Maharani Puspa Dewi; Siti Komariyah (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Bullying is a serious problem that often occurs in elementary school environments and has a negative impact on students' mental growth and academic achievement. This article aims to describe strategies for handling bullying through coaching activities for fourth-grade students of SDN Sertajaya 03, Cikarang. The method used is a quantitative approach with a pre-test and post-test design involving 22 respondents. A questionnaire instrument was used to measure students' understanding and behavior before and after coaching. The results showed an increase in students' knowledge about bullying from 54.5% to 77.3% in the good category, as well as an increase in positive attitudes towards handling bullying from 63.6% to 72.7%. This activity proves that providing education through coaching is effective in increasing students' understanding and behavior towards bullying. Thus, educational interventions like this can be a significant preventive strategy in creating a safe and comfortable school environment.